Kształcenie w zakresie projektowania książki w grafice użytkowej w szkolnictwie Warszawy w latach międzywojennych - Boguszewska, Anna (Biuletyn Historii Wychowania, 2010)
The article is devoted to the history of artistic educational system in Warsaw in the inter-war period. The author analyses the methods of teaching the students of applied arts how to insert graphic elements in books. The following institutions are taken into account: Miejska Szkoła Sztuk Zdobniczych i Malarstwa, Warszawska Szkoła Sztuk Pięknych, Doświadczalna Pracownia Graficzna operating in Salezjańska Szkoła Rzemiosł, Szkoła Przemysłu Drukarskiego and the W. Gerson Szkoła Sztuk Pięknych. The abovementioned public and private artistic schools followed varied educational programmes – from a three-year vocational school specializing in arts to an academic level. The educational concepts were connected with the recognition of an important role of applied arts in social life, also in the aspect of visual culture. A well-developed artistic educational system made Warsaw an important printing centre.